Women Behind Terrorists (Religiousity, Self Adaptation and Husband-Wife Relationship within Suspected Terrorists Family in Pekalongan) - Maghfur Maghfur; Siti mumun Muniroh (Analisa: Journal of Social Science and Religion, 2013)
Women and their religiosity are questioned along with the proliferation of conflict, violence, and religion-based riots which allegedly involving ‘husband’  suspected  terrorists. This article discusses the religiosity of the wives, the adjustment of wives of suspected terrorists against psychological and social burden, and the patterns of marital relations of terrorist suspects in Pekalongan-Central Java. The result of this phenomenological study revealed that the religiosity of terrorist-suspects’ wives are more dominant is exclusive patterned- if it is compared to moderate or inclusive ones. In terms of adjustment, the wives are just accept the fate and tend to be indifferent to the activities of their husbands. The wives also nullifying the public’s negative perception and judgment, but some are closed to the social interaction. While the pattern of relationships that were frequently built tent to be more owner property and head-complement in characteristics. Wives are positioned as husband’s complement for all activities in the fields of social, religious and political.